2017
DOI: 10.1108/ejm-05-2016-0264
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty avoidance and the exploration-exploitation trade-off

Abstract: Uncertainty Avoidance and the Exploration-Exploitation Trade-off AbstractPurpose -This study investigates how a firm's uncertainty avoidance -as indicated by the headquarters' national culture -impacts firm performance by affecting exploratory (product innovation) and exploitative (brand trademark protection) activities. It aims to show that firms characterized by high levels of uncertainty avoidance may be less competitive in the exploratory product development stage, but may be more competitive in the exploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Several cross-cultural researchers have examined the influence of national culture on innovative practices of firms (Broekhuizen et al, 2017;Shane, 1993;Zhu et al, 2018). Studies find innovative practices that differ across countries can be explained by the manifestation of national culture within a country's firms.…”
Section: Impact Of National Culture On Entrepreneurial Innovativenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Several cross-cultural researchers have examined the influence of national culture on innovative practices of firms (Broekhuizen et al, 2017;Shane, 1993;Zhu et al, 2018). Studies find innovative practices that differ across countries can be explained by the manifestation of national culture within a country's firms.…”
Section: Impact Of National Culture On Entrepreneurial Innovativenessmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first academic endeavor to investigate the influence of all six cultural values on EI among Malaysian Chinese, Malay, and Indian entrepreneurs in a systematic and comparative manner. Such systematic analysis enabled us to paint a fuller picture of how national cultural values influence SMEs' innovation and specifically the innovative activities of their entrepreneurs (Broekhuizen et al, 2017;Tian et al, 2020;Watts et al, 2020;Zhu et al, 2018). The novelty of this study may be further enhanced because we also offer insights to researchers and practitioners through a fine-grained analysis of three different ethnic groups in their EI.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, new products cause higher uncertainty than do existing products. Members in high-UA societies consider novel and innovative things as dangerous and suspicious and hence, resist them, while members in low-UA societies are more open to change and new ideas (Efrat, 2014;Broekhuizen, Giarratana, Torres, 2017). Therefore, it is reasonable to assume that consumers are less confident regarding changes in creative new products in a high-UA society and thus refrain from activities involving creative products.…”
Section: Moderating Effect Of Uncertainty Avoidancementioning
confidence: 99%
“…He explains the success of IBM in the personal computer not with IBM's technological superiority but with IBM's legitimacy "with corporate clients who had previously invested in IBM's mainframe computers" (p. 1221). In an industry like security software, Broekhuizen et al (2017) have shown the importance of firm names as anchors of company reputation and legitimacy, especially in terms of resilience and soundness. As we mentioned, by resorting to arms' length contracts, a specialist can focus on customization, obtain financial resources, and maintain its identity while leveraging the applicability of its technology to other product domains.…”
Section: Technology Trading and Survivalmentioning
confidence: 99%